Parasitic Leiomyoma: A Case Report - Kaudel, Sudeep; Rana, Aparihayra (Journal of College of Medical Sciences-Nepal, 2021)
ABSTRACT: Parasitic or wandering leiomyoma are rare extra-uterine benign pedunculated sub-serous leiomyoma which after being detached from its primary location thrives in secondary location from blood supply from nearby feeding vessels. This case represents a multiparous woman, with one such parasitic leiomyoma encountered at laparotomy, proven by histopathological examination.